Mechanisms Driving Karyotype Evolution and Genomic Architecture - Ruiz-Herrera, Aurora; Farré-Belmonte, Marta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Understanding of the origin of species and their adaptability to new environments is one of the main questions in biology. This is fueled by the ongoing debate on species concepts and facilitated by the availability of an unprecedented large number of genomic resources. Genomes are organized into chromosomes, where significant variations in number and morphology are observed among species due to large-scale structural variants such as inversions, translocations, fusions, and fissions. This genomic reshuffling provides, in the long term, new chromosomal forms on which natural selection can act upon, contributing to the origin of biodiversity. This book contains mainly articles, reviews, and an opinion piece that explore numerous aspects of genome plasticity among taxa that will help in understanding the dynamics of genome composition, the evolutionary relationships between species and, in the long run, speciation.